THE CAPACITY OF ENGLISH SUBJECT TEACHERS’ WORKING GROUP (MGMP) IN SUPPORTING TEACHER PROFESSIONAL DEVELOPMENT (A Case Study of English MGMP of Senior High Schools in Kota Pontianak) - Rodhi Rodhi (IKIP PGRI Pontianak, 2015)
This case study was designed to describe a) the organization structure of English Subject Teachers’ Working Group 9MGMP0 of senior high schools; and b) how English MGMP of senior high schools utilized its capacity and functions in promoting teacher professional development (TPD) of the members. The study involved six teachers selected randomly as participants from the accessible schools. Interviews and documentation were employed to collect the data. In one side the findings summarize that in general all the repondents asserted the benefits of MGMP forums for classroom practices. In the other side, nevertheless, the findings conversely conclude that MGMP capacity and functions were not optimally made use for promoting TPD as a result of being unwell managed in terms of personnel, program schedules, and program coverage and of being insufficiently supported by local authority of education in terms of regular mentoring towards MGMP activities and management. Key words: Teacher Professional Development, Teacher Competence, Subject Teachers’ Working Group (MGMP), MGMP Capacity.